A Composite Modeling Analysis of the Deformation Behavior of Medium Manganese Steels. Issue 10 (13th April 2015) - Rana, Radhakanta; Gibbs, Paul J.; De Moor, Emmanuel; Speer, John G.; Matlock, David K.; Bleck, Wolfgang
<x xml:space="preserve">Abstract</x> A composite model with different assumed flow behaviors for the individual microstructural constituents and stability parameters for the metastable austenite transformation is presented and shown to provide design insight into the development of third‐generation advanced high strength steels with a wide spectrum of tensile properties. The deformation behavior of a Fe‐7.09 Mn‐0.099 C‐0.13 Si (wt%) steel is evaluated with uniaxial tensile testing and the results are correlated with predictions of the composite model. It is shown that the present simple composite model can predict tensile strength and uniform elongation with good accuracy over a range of austenite volume fractions in the steel. The analysis is based on Mn enrichment into austenite during intercritical annealing of the steel resulting in microstructures with significant variations in the amount and stability of austenite. Strategies for controlling the stability and amount of austenite in medium Mn steels are also presented in low carbon, nominally 5–10 wt% Mn‐containing steels with/without Al as an alloying addition.